The Protective Anticancer Effect of Natural Lycopene Supercritical CO2 Watermelon Extracts in Adenocarcinoma Lung Cancer Cells - Caterina Di Sano; Valentina Lazzara; Miriana Durante; Claudia D'Anna; Angela Bonura; Paola Dino; Carina Gabriela Uasuf; Elisabetta Pace; Marcello Salvatore Lenucci; Andreina Bruno (MDPI AG, 2022)
Carotenoids may have different effects on cancer and its progression. The safety of carotenoid supplements was evaluated in vitro on human non-small cell lung cancer (NSCLC) adenocarcinoma A549 cells by the administration of three different oleoresins containing lycopene and other lipophilic phytochemicals, such as tocochromanols. The oleoresins, obtained by the supercritical CO2 green extraction technology from watermelon (Lyc W), gấc(Lyc G) and tomato (Lyc T) and chlatrated in α-cyclodextrins, were tested in comparison to synthetic lycopene (Lyc S), by cell cycle, Annexin V-FITC/PI, clonogenic test, Mytosox, intracellular ROS, Western Blot for NF-kB and RT-PCR and ELISA for IL-8. The extracts administered at the same lycopene concentration (10 µM) showed conflicting behaviors: Lyc W, with the highest lycopene/tocochromanols ratio, significantly increased cell apoptosis, mitochondrial stress, intracellular ROS, NF-kB and IL-8 expression and significantly decreased cell proliferation, whereas Lyc G and Lyc T significantly increased only cell proliferation. Lyc S treatment was ineffective. The highest amount of lycopene in Lyc W was able to counteract and revert the cell survival effect of tocochromanols supporting the importance of evaluating the lycopene bio-availability and the real effect of antioxidant tocochromanols' supplementation which may not only have no anticancer benefits but may even increase cancer aggressivity.